Strategi Bimbingan Tokoh Agama di Bangka Belitung: Kontestasi dalam Masyarakat Pedesaan - Rozi, Rozi (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2020)
This discourse aims to describe the strategy of Guru Zuhri and Ustaz Fathur Rozi in providing Islamic guidance to the people of Kayu Besi Village, Puding Besar District, Bangka Regency, Bangka Belitung Islands, examining the contestation that the two have done to gain community legitimacy, and analyzing the extent of the contestation of the two figures. religion in Bangka Belitung. This research uses qualitative research with a field research approach. As for data collection techniques, the authors used in-depth interviews, participatory observation and documentation. The results showed that in providing Islamic guidance to the community, Guru Zuhri did not just provide religious advice. However, he also provides assistance to various problems faced by members of the guidance and village community, both personal, family, social, and especially religious issues. Meanwhile, the provision of Islamic guidance carried out by Ustaz Fathur Rozi was only limited to giving religious advice or it could be said by recitation. Guidance is given not to touch aspects of community life. In the sense that it does not solve problems for problems that develop in life, either individuals or groups of people. In addition, in providing Islamic guidance to rural communities, the two of them both contest each other to gain community legitimacy. The contestation is real. There are three forms of contestation that occur in both of them, namely: First, the contestation of wisdom. Second, power contestation. Third, ideological contestation. At the end of the contestation story, Guru Zuhri got more and more legitimacy from the community for his character. Meanwhile, Ustaz Fathur Rozi lost legitimacy from the community, so he tried again to build that legitimacy.